2018
DOI: 10.1016/j.jtcvs.2017.08.144
|View full text |Cite
|
Sign up to set email alerts
|

Cost of individual complications following coronary artery bypass grafting

Abstract: The average cost of CABG without complication was $36,580. Each additional major complication resulted in an exponential increase in cost. Over the past 10 years, the total cost of complications after isolated CABG was $78.6 million, emphasizing the importance of quality improvement projects to contain costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 22 publications
4
51
0
2
Order By: Relevance
“…Several studies have identified postoperative complications and resource utilisation as the largest drivers of healthcare cost 42–44. To offer optimal value in healthcare we must provide the highest quality care at the lowest cost.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified postoperative complications and resource utilisation as the largest drivers of healthcare cost 42–44. To offer optimal value in healthcare we must provide the highest quality care at the lowest cost.…”
Section: Discussionmentioning
confidence: 99%
“…The VCSQI database (ARMUS Corporation, San Mateo, CA) captures STS demographic, preoperative, clinical, and 30-day outcomes data on patients who undergo cardiac surgery at 18 centers in Virginia and 1 center in North Carolina. [19] Cost data derived from Uniform Billing-04 files, which identifies charges classified by International Classification of Diseases ninth revision-based revenue codes, are matched to STS data. [20] Costs are estimated using cost-to-charge ratios submitted to Centers for Medicare and Medicaid Services.…”
Section: Study Populationmentioning
confidence: 99%
“…[1][2][3][4] Negative pressure wound therapy 3,5,6 and advances in reconstructive surgery of the sternum may improve the outcome of patients with postoperative DSWI, 7,8 but hospital and late mortality in these patients remains nonnegligible. [9][10][11][12][13] Furthermore, the financial burden associated with the treatment of sternal wound complications is relevant due to the direct costs incurred by the related prolonged therapies and hospital stay. 9,10,14 In this context, effective preventive strategies along with a tailored method of DSWI risk stratification are of utmost importance.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] Furthermore, the financial burden associated with the treatment of sternal wound complications is relevant due to the direct costs incurred by the related prolonged therapies and hospital stay. 9,10,14 In this context, effective preventive strategies along with a tailored method of DSWI risk stratification are of utmost importance. In particular, identification of high-risk patients is important when bilateral internal mammary artery (BIMA) grafting is planned because the risk of DSWI is higher with this technique.…”
mentioning
confidence: 99%